The Federal Republic of Germany and NATO : 40 years after - Kirchner, Emil J., 1942- 19.03.1942- (Macmillan, 1992)
The Federal Republic of Germany and NATO is a systematic effort to explore the domestic, regional, and systemic factors shaping Germany's role in NATO. This book, initially intended as a stocktaking of West Germany's interest and role in NATO over a forty-year period, was transformed by events into a retrospective of what NATO has meant for West Germany and its partners between 1949 and 1989, and what NATO may mean in the future for a unified Germany, for a Europe spanning the Atlantic to the Urals, and for the United States. The book provides the reader with a sound historical basis for reaching reasonable conclusions about the questions raised by the unfolding of the post-postwar order.